Acarine biocontrol agents Neoseiulus californicus sensu Athias-Henriot (1977) and N. barkeri Hughes (Mesostigmata: Phytoseiidae) redescribed, their synonymies assessed, and the identity of N. californicus (McGregor) clarified based on examination of types - Beaulieu, Frédéric; Beard, Jennifer J. (Zootaxa, 2018)
In 1954, McGregor described two species of phytoseiids from lemon, in California, USA: Typhlodromus californicus McGregor and T. mungeri McGregor, the former represented by one male, and the latter by two females. Since its description, T. mungeri was synonymised under T. californicus, and the name T. (now Neoseiulus) californicus has been used extensively to represent a species that is now commonly used as a biocontrol agent of crop pests worldwide. However, the true identity of the biocontrol agent is uncertain because the original descriptions of T. californicus and T. mungeri were not adequate enough to allow an irrefutable identification, with each description being based on specimens of a single sex. An examination of the types of N. californicus and N. mungeri revealed that they are morphologically identical to the male and female of N. barkeri Hughes, 1948, respectively, and that they are in fact junior synonyms of N. barkeri—and are therefore distinct from the biocontrol agent globally called N. californicus (sensu Athias-Henriot, 1977; see Griffiths, 2015). This is further supported by a comparison with male and female syntypes of N. barkeri, as well as other specimens of N. barkeri including some collected from the type host in the vicinity of the type location (i.e. lemon in southern California, 1952–1958). We redescribe the male and female of both N. barkeri and N. californicus sensu Athias-Henriot (1977), based on representative specimens from at least 14 and 19 populations, respectively. Based on examination of types, we confirm the synonymy of N. mckenziei (Schuster & Pritchard, 1963), N. picketti (Specht, 1968), and N. oahuensis (Prasad, 1968) with N. barkeri, and that the names N. chilenensis (Dosse, 1958b) and N. wearnei (Schicha, 1987) represent the same species as N. californicus sensu Athias-Henriot (1977). We also provide a hypothesis as to why Chant (1959) had erroneously synonymised T. californicus and T. mungeri under T. marinus (Willmann). Finally, we suggest maintaining the prevailing usage of the name N. californicus (McGregor) for the species concept of Athias-Henriot (1977) as followed by subsequent authors, through submission of a separate application to the International Commission of Zoological Nomenclature (ICZN). In the meantime, the current meaning of N. californicus should be maintained until a ruling by the ICZN is made on the application.